Presence of diabetic risk factors within a sample of community members in Windhoek, Namibia - Michelle C. Delpaul; Craig Vincent-Lambert (African Journal of Primary Health Care & Family Medicine)
Background: Non-communicable diseases (NCDs) continue to pose a significant challenge to global healthcare systems. In African contexts, diabetes ranks among the top four NCDs. The disease often goes undetected because patients are commonly asymptomatic in the early stages. Screening, early diagnosis and patient education may prolong life and reduce costs associated with managing the disease.